PROSPECTS OF CLOUDY TECHNOLOGIES IN THE SOLUTION OF THE TASK OF THE ANALYSIS OF LARGE VOLUMES OF THE DATA OBTAINED IN ASTRONOMICAL SUPERVISION - Isaev, E. A.; Kornilov, V. V.; Samodurov, V. A.; Tarasova, A. A. (Одеські астрономічні публікації, 2013)
In modern astronomy the problem of the big data obtained during scientific experiments is very actual. One of the perspective approaches to the solution of the problem of processing of superlarge volumes of experimental data in real time is the use of the technology of cloud computing which assumes ensuring remote dynamic access of users to services, computing resources and appendices on the Internet.